Dampak Pandemi Covid 19: (Studi Eksploratif terhadap Pembelajaran Bahasa Arab pada Sekolah Menengah Pertama di Lingkungan Pesantren) - Ummidlatus Salamah; Fashi Hatul Lisaniyah (Prodi. Pendidikan Bahasa Arab, 2022)
The impact of the Covid-19 pandemic has been felt by the world of education, including educational institutions in junior high schools located in Islamic boarding schools. Islamic boarding-based educational institutions relatively limit the use of electronic media and online media in their daily activities, including in the teaching and learning process. The impact felt is very large with the Covid-19 pandemic, where all learning activities must be carried out online. This is the background of the research conducted at the Islamic Junior High School Ma'arif NU Bustanul Muta'allimin Islamic boarding school Nguwok Lamongan. The purpose of this study is to find problems faced by students and teachers in the pesantren environment and provide solutions that help in the learning process. The research method used is descriptive qualitative, using an exploratory case study. The result of this research is that students do not understand the material taught by the teacher through online learning. The students stated that online learning was not fun because the learning was not interesting, so that students became bored with doing online learning. While the impact felt by the teacher, namely learning becomes ineffective, material is not delivered perfectly due to limitations of learning media, teacher work becomes unlimited, internet connection is hampered, and difficulty to practice in the laboratory. The solutions offered are in the form of media to make learning more effective, including learning media for Google classroom, Kahoot, Socrative, Canva, and PhET Simulation.